Influence of political knowledge on civil servant's perceptions towards Nigerian federalism among civil servants in Bauchi state, Nigeria - Ahmad Aliyu, Aisha; Ismail, Mohd Mahadee; Md Nor, Mohd Sabri (Human Resource Management Academic Research Society, 2022)
In Nigeria, the renewed calls and agitations from diverse sectors for the restructuring of Nigerian federalism has over the years been characterized by numerous inconsistencies and tensions. This study was designed to determine the influence of political knowledge on the perceptions of Bauchi state civil servants towards Nigerian federalism. A total of 396 respondents were selected through a stratified sampling technique from the population of 96,728. Data was collected using a set of questionnaires. Correlation and multiple regressions were used to analyze the data. The research unveils that, political structural knowledge has a positive and significant relationship with respondents’ perception of federalism in Nigeria while political factual knowledge has a significant and positive relationship with citizens’ perception of Nigerian federalism. The multiple regression results showed that political structural knowledge (B=.219, P<.001) and political factual knowledge (B=.614, P<.001) were found to be significant. The result has shown that among the predictors of federalism political factual knowledge is the highest predictor. Hence, it is recommended that the government design an enlightenment program targeting civil servants in Bauchi state in order to educate them and enhance their understanding and perception of Nigerian federalism.